Enhancing productivity of rainfed farms by adopting bael + cowpea horti-agri system strengthened with water conservation practices - Sudhishri, Susama; Singh, Man; Dass, Anchal; A S, Naqibullah; Usha, K. (Indian Farming, 2018)
Rainfed agriculture constitutes the source of food and livelihood security of millions of people worldwide. However, production of rainfed areas is constrained by the extreme variability in rainfall, poor nutrient status of soils, land degradation through erosion etc. Under such situations, horti-agri and other agroforestry land use systems are the best options to protect the land from various types of degradation, diversifying the farming system and increasing the soil carbon build up and moisture storage. These benefits of agroforestry can be improved by incorporating in-situ moisture conservation practices and legume crops intercropped with fruit trees may provide important source of cash and income. In a field experiment carried out at Research Farm, Water Technology Centre, Indian Agricultural Research Institute, New Delhi during kharif of 2015 and 2016 with cowpea grown in bael tree orchard provided with contour trench on its upper side of bael tree rows for water conservation, inclusion of cowpea enhanced the bael fruit yield and also the total yield (bael + cowpea) expressed as cowpea greenpod equivalent yield, when the plots were provided with contour trench treatment for water conservation. The study demonstrated that bael tree or any other hardy horticulture intercropped with cowpea and the system supported with contour trench water conservation practice in the upstream of tree can immensely increase farm productivity and income under rainfed conditions of arid and semi-arid climate.